2012
DOI: 10.1080/10503307.2011.653996
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent adherence to psychosocial treatment: Mental health clinicians' perspectives on barriers and promoters

Abstract: Poor adolescent adherence to mental health psychosocial treatment significantly undermines effectiveness. Approximately one-third of all youth drop out or prematurely terminate from psychosocial treatment. This study examined youth adherence to psychosocial treatment from the perspective of community-based mental health clinicians (n =34) interviewed across three focus groups. A grounded theory analysis was applied to investigate the promoters and barriers influencing adolescent adherence to treatment. Clinici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 54 publications
2
23
0
5
Order By: Relevance
“…Researchers found that adolescent clients who were motivated to continue treatment and who held positive expectations of the process were more likely to adhere to treatment (Gearing et al 2012). If providers can motivate youth to see the value of treatment and help them understand that there can be positive outcomes, they may be less likely to terminate prematurely.…”
Section: Discussionmentioning
confidence: 96%
“…Researchers found that adolescent clients who were motivated to continue treatment and who held positive expectations of the process were more likely to adhere to treatment (Gearing et al 2012). If providers can motivate youth to see the value of treatment and help them understand that there can be positive outcomes, they may be less likely to terminate prematurely.…”
Section: Discussionmentioning
confidence: 96%
“…In the Netherlands about 10% of these adolescents receive psychosocial care for emotional or behavioral problems [2,3]. However, clients often display poor treatment adherence, and approximately one-third of all adolescents drop out from psychosocial care, undermining the effectiveness of treatment [4,5]. Care may be more effective if clients participate actively, for instance, by keeping scheduled appointments and adhering to recommendations [4].…”
Section: Introductionmentioning
confidence: 99%
“…More generally, it is estimated that 20% to 70% of persons, across all age groups and diagnoses, who begin psychosocial mental health treatment discontinue such treatment against their clinicians' recommendations (222). For adolescents specifically, a study suggests that about a third of patients in mental health psychosocial treatments dropout prematurely (223). A systematic review that included 25 studies of non-completion among PD treatments found a median non-completion rate of 37% (224).…”
Section: Taking the Dodo Bird Serious: Effective Ingredients And Commmentioning
confidence: 99%